Penerapan Perencanaan dan Penganggaran Responsif Gender pada RPJM di Provinsi Kepulauan Bangka Belitung - Wenni Anggita; Duwi Agustina; Anggraeni Yunita (Accounthink : Journal of Accounting and Finance, 2022)
The National Women's Machinery which always promotes and implements national planning and budgeting by including a gender perspective. Support for the implementation of gender responsive budgeting, also echoed by Women's PPB which includes members of civil society and women's organizations to share information and exchange ideas for the country's future. Efforts in coordinating the Joint Program to achieve the Millennium Development Goals, which consist of UNDP, UNFPA, UNICEF, and IOM also increase the involvement of UN Women as leaders in working with governments to mainstream budgets, policies and programs. UN Women also supports women's organizations and NGOs that work on transparency in government budgets and  business in private sector. In 2013 Bangka Belitung gender development index (IPG) ranks 30th in Indonesia, indicating a gap between men and women in enjoying the fruits of development in the regions. Bangka Belitung became one of the two provinces selected as piloting the implementation of PPRG at the village level in addition to Gorontalo Province. Based on the explanation that has been explained then in this study explaned that the application of PPRG in the village fund budget in the Bangka Belitung by identifying 7 PUG indicators contained in the Regional RPJM.